Research on the macro-microscopic mechanical characteristics and correlations of warm frozen soil under dynamic and static loads - Hu Zhang; Lijun Xing; Shengjin Zhang; Jintao Hu; Jun Zhao; Lang Dai; Zheng Li; Feng Liu (Alexandria Engineering Journal, 2025)
Both static and dynamic loads affect the stability of foundations in warm frozen soil areas. However, research on warm frozen soil mainly focuses on macroscopic experiments, with little attention given to the micro-deformation behavior under such loads. This study uses temperature and load as the primary factors and conducts dynamic and static triaxial compression tests to analyze the mechanical properties and dynamic evolution of pore-water pressure (PWP) in warm frozen soil. A logistic regression model is used to fit the relationship between PWP and strain. Finally, Micro-CT technology is applied to observe the microstructural changes and microcrack development in warm frozen soil under both static and dynamic loads. The results indicate that as axial pressure increases, PWP also increases, while lower ambient temperatures result in lower PWP levels. Under dynamic loads, the fluctuation of PWP is more pronounced, with its rate diminishing over time, while under static loads, it continues to grow. Despite variations in sample properties, the average PWP and strain ratios under both dynamic and static loads are comparable. The ambient temperature of the sample has a greater impact on the differences in PWP and strain than the load magnitude. PWP and strain exhibit a strong correlation, with both fitting well to the logistic regression model. Microcrack development in the samples is more pronounced under dynamic loads, with cracks being larger in size compared to those formed under static loads. These findings provide theoretical support for earthquake engineering safety assessments in cold regions, as well as for disaster prevention and mitigation in transportation engineering.